2019
DOI: 10.3389/fevo.2019.00189
|View full text |Cite
|
Sign up to set email alerts
|

Shotgun Environmental DNA, Pollen, and Macrofossil Analysis of Lateglacial Lake Sediments From Southern Sweden

Abstract: The lake sediments of Hässeldala Port in south-east Sweden provide an archive of local and regional environmental conditions ∼14.5-9.5 ka BP (thousand years before present) and allow testing DNA sequencing techniques to reconstruct past vegetation changes. We combined shotgun sequencing with plant micro-and macrofossil analyses to investigate sediments dating to the Allerød (14.1-12.7 ka BP), Younger Dryas (12.7-11.7 ka BP), and Preboreal (<11.7 ka BP). Number of reads and taxa were not associated with sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
95
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(109 citation statements)
references
References 55 publications
8
95
0
4
Order By: Relevance
“…Slon et al (2017), assigned more than 10% of their shotgun reads that derived from cave sediments and Ahmed et al (2018) reported 16% of assigned sequences from ancient lake sediments and 70% of hits over multiple taxa. On the other hand, Pedersen et al (2016) assigned 0.3% of the quality filtered reads obtained from ancient lake sediments, and Parducci et al (2019) reported a read assignment of 3.4% of sedaDNA shotgun sequencing. Different sample material, wet lab processing and sequence databases used for assignment make it difficult to properly compare the assignment rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Slon et al (2017), assigned more than 10% of their shotgun reads that derived from cave sediments and Ahmed et al (2018) reported 16% of assigned sequences from ancient lake sediments and 70% of hits over multiple taxa. On the other hand, Pedersen et al (2016) assigned 0.3% of the quality filtered reads obtained from ancient lake sediments, and Parducci et al (2019) reported a read assignment of 3.4% of sedaDNA shotgun sequencing. Different sample material, wet lab processing and sequence databases used for assignment make it difficult to properly compare the assignment rate.…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing of the entire DNA extracted from ancient sediments, termed metagenomic shotgun sequencing, has been shown to provide information on the entire taxonomic composition of the sample (e.g., fungi, bacteria, archaea; Ahmed et al 2018;Parducci et al 2019). By sequencing complete DNA molecules, it is possible to authenticate ancient sequences versus modern contaminants by their specific postmortem DNA damage patterns towards the ends of the molecules (Ginolhac, Rasmussen, Gilbert, Willerslev, & Orlando, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are few pipelines available for the analysis of ancient metagenomic DNA (aDNA) [1][2][3][4] The limited number of bioinformatic pipelines for aDNA metagenomics can be attributed to a low yield of DNA compared to that achieved in modern metagenomic DNA extraction. This results in the use of high-cost DNA capture techniques to improve aDNA yields to levels suitable for bioinformatic assessment [3][4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Those metagenomic studies performed using DNA capture techniques, necessary for existing bioinformatic pipelines, allow for the implementation of "quick" bioinformatic comparisons using RefSeq or Blastn megablast options due to higher yields of DNA [5][6][7] . Due to higher yields, however, these pipelines, by their nature, often compromise between read conservation and processing time, thus losing sequences throughout individual computational steps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation